Reducing meat consumption in Central Asia through 3D printing of plant-based protein—enhanced alternatives—a mini review - Auyeskhan, Ulanbek; Azhbagambetov, Arman; Sadykov, Temirlan; Dairabayeva, Damira; Talamona, Didier; Chan, Mei-Yen (Frontiers in Nutrition, 2024)
3D food printing (3DFP) is emerging as a vital innovation in the food industry's pursuit of sustainability. 3DFP has evolved to significantly impact food production, offering the capability to create customized, nutritionally balanced foods. Central Asia has a higher than global average level of meat consumption per capita, which might be influenced by its historical and cultural background of nomadism. This dietary trend might potentially result in negative impacts on both the environment and human health outcomes, as it leads to increased greenhouse gas emissions, higher water footprint, biodiversity loss as well as increased risk of chronic diseases. Reducing meat consumption holds the potential to address these health and sustainability issues. A possible strategy to reduce meat consumption and promote plant-based foods is 3D Food Printing (3DFP), which can rely on plant-protein sources from the region to create appealing and tasty alternatives for these populations. This review summarizes recent studies on plant protein-rich materials for 3DFP as a substitute to meet the growing global demand for meat as well as the 3DFP printing parameters associated with the different plant-based proteins currently used (e.g. lentils, soybeans, peas, and buckwheat). The findings revealed that buckwheat, a dietary staple in Central Asia, can be a promising choice for 3DFP technology due to its widespread consumption in the region, its gluten-free nature, and highly nutritious profile as well as its optimal composition for 3DFP.